Synthesis of substituted triazole–pyrazole hybrids using triazenylpyrazole precursors - Gräßle, Simone; Holzhauer, Laura; Wippert, Nicolai; Fuhr, Olaf; Nieger, Martin; Jung, Nicole; Bräse, Stefan (Beilstein Journal of Organic Chemistry, 2024)
A synthesis route to access triazole–pyrazole hybrids via triazenylpyrazoles was developed. Contrary to existing methods, this route allows the facile N-functionalization of the pyrazole before the attachment of the triazole unit via a copper-catalyzed azide–alkyne cycloaddition. The developed methodology was used to synthesize a library of over fifty new multi-substituted pyrazole–triazole hybrids. We also demonstrate a one-pot strategy that renders the isolation of potentially hazardous azides obsolete. In addition, the compatibility of the method with solid-phase synthesis is shown exemplarily.
Keywords: azide; click reaction; CuAAC; pyrazole; triazene; triazole